Understanding Hypervolemia in Chronic Kidney Disease - Ika Ainur Rofi'ah Ainur Rofi'ah, M.Kep., Sp.Kep.M.B (EZRA SCIENCE BULLETIN, 2023)
Introduction: Chronic Kidney Disease (CKD) is a progressive and irreversible decline in kidney function and a decreased Glomerular Filtration Rate (GFR). Decreased kidney function contributes to decreased water excretion and fluid overload caused by decreased GFR. A progressive decrease in GFR in renal disease leads to hypertension, sodium retention, and fluid overload. Discussion: CKD is kidney damage or also defined as a decrease in glomerular filtration rate (GFR) of less than 60 ml/minute/1.73m2 that occurs for 3 months or more. CKD is most caused by Diabetes Mellitus 64.1% and Hypertension 80.7%. One clinical manifestation in patients with CKD is an increase in fluid volume (hypervolemia). Hypervolemia is one of the nursing problems in the nursing care process. Based on the Indonesian Nursing Diagnosis Standard Book, hypervolemia is an increase in intravascular, interstitial, and/or intracellular fluid volume. The etiology of hypervolemia in CKD patients is a regulatory mechanism disorder associated with decreased GFR. Signs and symptoms both major and minor in hypervolemia nursing problems show that most patients have peripheral oedema of 53.8%, the prevalence of anemia is 52.3%, the prevalence of Haemoglobin 7-10 mg/dl is 68.3%, and the prevalence of oliguria is 16.3%. One of the actual nursing diagnosis in patients with CKD is hypervolemia related to the disturbance of regulatory mechanisms (a decrease in GFR). A progressive decrease in GFR can lead to sodium and fluid retention which causes fluid balance disturbances.